Milking Versus Delayed Cord Clamping in Full Term Neonates Delivered by Elective Caesarean Section a Randomized Controlled Trial - Ahmed M El-kotb (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Background: Preterm birth is a major health concern. It is the leading cause of perinatal mortality and morbidity. Besides varied etiology, it may be due to alteration in basic biochemical function of the body at cellular level stating emphasis to trace elements of which magnesium, being one of them. Pregnancy is marked by a state of hypomagnesaemia and varied hypomagnesaemia observed in preterm labor cases.  Aim of the work: The study conducted to find out the relationship between low serum magnesium concentrations with preterm labor.  Methods: It is a cross-sectional case-control study in which eligible participants were 200 pregnant women attended to El Galaa Teaching Maternity Hospital 100 of them admitted in preterm labor (Case), while the other 100 had normal antenatal care and completed their pregnancy till 37 weeks at least (control), relevant data were extracted from the case records of these women and blood samples were obtained from all participants and serum magnesium levels measured.  Results: The study showed that 36% of the study patients had varying degrees of hypomagnesaemia. The relative risk indicates that preterm labor is 1.83 times higher among the patients with low serum magnesium (less than 1.6 mg/dL).The mean difference in serum magnesium levels in both groups was statistically significant (P < 0.05).  Conclusion: Low serum magnesium (hypomagnesaemia) is associated with preterm onset of labor. We can, also from this finding, formulate a proposition that would help in preventing preterm labor and birth with the use of prophylactic oral magnesium supplementation among patients with higher risk for development of preterm labor.